Fotometria para biologistas - Cardoso, Victor José Mendes [UNESP] (Oecologia Australis, 2009)
Most life-sustaining energy on Earth comes from the Sun. Part of this energy is converted by plants via photosynthesis into chemical energy. Many scientific studies on photosynthesis by plants rely on an accurate description of the quantity and quality of incident light, which in turn depends on the use of proper terminology for describing the luminous nature of the organism or population in question. Although the scientific literature contains a number of references on this matter, it is still fairly common to find misinterpretations and errors involving the application of terms used for describing light in scientific experiments. I herein present and discuss much of this specialized terminology, such as the terms 'radiation', 'luminous intensity', 'irradiance'. in order to assist readers who seek to understand and make use of this terminology properly.
Photometrics for biologists
Keywords: Irradiance; Light; Proficiency; Radiation; Units